Conflicts Of Cultural Values Reflected In Jhumpa Lahiri's The Namesake: A Sociological Study Of Literature - Nurpermadi, Erwin Dwi, Dr. M. Thoyibi, M.S, Mauly Halwat Hikmat, Ph. D (2014)
The research is proposed to analyse conflicts of cultural values in "The Namesake" novel by using Sociological Perspective. The major problem in this article is to explain how the conflicts of cultural values happen in Jhumpa Lahiri's "The Namesake". The object of study is "The Namesake" novel written by Jhumpa Lahiri. Qualitative study is a method which is used to analyze conflicts of cultural values reflected in the novel. The primary data is taken from the novel itself and the secondary data sources are other resources related the study such as dictionary, website, some books that support the analysis. The techniques of collecting data are reading the original novel several time, determining the character that will be analyzed, taking note of the important thing both the primary data and secondary data, and classifying and determining the relevant data. The techniques of data analysis are as follows: the first is analyzing of the novel, the second is analyzing the data based on sociological perspective. The results of this study are, first, based on the structural analysis of each element, it shows that the character and characterization, setting, plot, point of view, style, and theme are related to each other and form the unity into a good quality novel. Second, based on Sociological Perspective, the conclusion is that the second generation of Indian immigrant in America prefer to use Indian culture but the second generation of Indian prefer to use American culture.